A new cave-dwelling millipede of the genus Scutogona from central Portugal (Diplopoda, Chordeumatida, Chamaesomatidae) - Enghoff, Henrik (2018)
A new cave-dwelling species of the genus Scutogona Ribuat, 1913, S. minor n. sp., is described from caves of Sicó karst in central Portugal. The classification and delimitation of Scutogona vis-à-vis related genera, in particular Meinerteuma Mauriès, 1982, is discussed.